The structure of an online assessment of science and social studies content: testing optional formats of a general outcome measure - Mooney, Paul; McCarter, Kevin S.; Russo, Robert J.; Blackwood, Danielle L. (Social Welfare: Interdisciplinary Approach, 2014)
Research questions addressed the structure of an online form of content-focused general outcome measurement known as critical content monitoring. The assessment tool is designed to serve as an accurate and efficient measure learning performance and progress in science and social studies classes. Scores from single administrations of critical content monitoring probes that varied in content and length were correlated with results from a statewide accountability content test for a sample of American fifth-grade students. The magnitude of correlation was moderate for probes that included a single content (i.e., social studies) or a mix of two subjects (i.e., social studies and science). Comparable correlations were reported for probes that featured reduced time or increased questions. Limitations and research implications are discussed.
Keywords: Content Area Assessment; Formative Assessment; Technology